2011
DOI: 10.1093/toxsci/kfr103
|View full text |Cite
|
Sign up to set email alerts
|

Joint Effects of Heterogeneous Estrogenic Chemicals in the E-Screen—Exploring the Applicability of Concentration Addition

Abstract: In the last few years, significant advances have been made toward understanding the joint action of endocrine disrupting chemicals (EDCs). A number of studies have demonstrated that the combined effects of different types of EDCs (e.g., estrogenic, antiandrogenic, or thyroid-disrupting agents) can be predicted by the model of concentration addition (CA). However, there is still limited information on the effects of mixtures of large numbers of chemicals with varied structural features, which are more represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…When compounds interact additively, one compound can be replaced with a fraction of an equally effective concentration of another compound without changing the overall combined effect. Second, some deviations from additivity may be expected (Charles et al, 2002;Kjaerstad et al, 2010), either in a negative direction due to an increased metabolism of natural steroidal estrogens in the mixture (Silva et al, 2011) or in a positive direction because of synergistic interactions related to additional interactions with the AR at receptor sites other than the ligand-binding domain (Orton et al, 2012). Consequently, it should be taken into account that the presence of each individual chemical residue at a "no-observed-adverse-effect level" does not necessarily imply a zero effect and does not rule out a potential impact of the mixture (Kortenkamp et al, 2007;Scholze et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…When compounds interact additively, one compound can be replaced with a fraction of an equally effective concentration of another compound without changing the overall combined effect. Second, some deviations from additivity may be expected (Charles et al, 2002;Kjaerstad et al, 2010), either in a negative direction due to an increased metabolism of natural steroidal estrogens in the mixture (Silva et al, 2011) or in a positive direction because of synergistic interactions related to additional interactions with the AR at receptor sites other than the ligand-binding domain (Orton et al, 2012). Consequently, it should be taken into account that the presence of each individual chemical residue at a "no-observed-adverse-effect level" does not necessarily imply a zero effect and does not rule out a potential impact of the mixture (Kortenkamp et al, 2007;Scholze et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This means that each individual component contributes to the global joint effect by acting in proportion to its concentration, even below concentrations producing no effect. This model has been used to assess combination effects of agents with a common site of action (Backhaus et al 2000b;Silva et al 2011a). Experimental evidence from some studies showed that combination effects of drugs with dissimilar mechanisms of action are better described using the alternative approach, that is, IA, which considers each agent interacting at differing sites of action (Backhaus et al 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…It is now accepted that a mixture of contaminants could induce more pronounced effects than the sum of its individual components. 3 However, very little is known about the effects of these mixtures of compounds in humans, as much of our knowledge is based on experimental studies of laboratory animals. For obvious reasons, it is not possible to expose humans to mixtures of compounds in a controlled fashion.…”
Section: Introductionmentioning
confidence: 99%